Embedded Sex Education in Pesantren: Students’ Meaning-Making and Pedagogical Implications - Mainuddin Mainuddin; Abdul Haris (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study examines how students interpret sex education that is integrated in pesantren learning and its pedagogical implications on the learning process at Pondok Pesantren Nurul Hakim West. This study uses a qualitative approach with a case study design. Data was collected through in-depth interviews with six students, observations, and documentation, then analysed using thematic analysis. The findings show that students generally do not know the formal term “sex education” or tarbiyah jinsiyyah, but understand the substance of the material through learning of Islamic jurisprudence (fiqh), manners (adab), pesantren rules, and biological material related to reproduction. For students, sex education is interpreted as a moral guideline to maintain awrah (parts of the body that should be covered according to Islamic teachings), personal hygiene, honor, and social boundaries, as well as practical knowledge that is relevant to daily life in the pesantren environment. Analysis through Piaget's theory of cognitive development and Bandura’s social cognitive theory shows that the effectiveness of sex education in pesantren is formed by two interrelated processes, namely the cognitive assimilation of material into the religious scheme that students already have and social strengthening through teacher example, discipline, supervision, and habituation in boarding life. The findings also show that student admissions are conditional: material is more readily accepted when framed in familiar moral-religious language, but learning comfort decreases when topics are conveyed too directly and through dominant lecture methods. This study concludes that sex education in pesantren is not determined by the formalization of terms, but by the integration of substance, religious framing, daily relevance, and pedagogical strategies. On that basis, this study offers the Pesantren-Embedded Sexuality Acculturation and Normative Learning Framework as a conceptual contribution to understanding value-based sex education in pesantren.